Difficulty Analysis Learning Mathematics Society and Factors Cause for Junior Secondary Students - Sariningtias, Rizki; Kusumawardani, Noviana; Yasfi, Ali; Syafaat, Agil; Aliyah, Ro’ikhatul (Proceeding International Conference on Science and Engineering, 2020)
The study aims to describe the type of learning difficulties and factors of the learning difficulties of students of class VII SMP N 4 Satu Atap Pakis in studying mathematics subjects on the set material. The type and approach in this research is a type of descriptive research with a qualitative approach. The data collection techniques in this study are with diagnostic tests, polls, and interviews. From the results of the study came the conclusion that the difficulties of students of class VII SMP N 4 Satu Atap Pakis in the material set is a) difficulty understanding the question b) difficulty understanding the mathematical symbols and can not find the keywords of the problem, c) difficulties Transforming the problem, d) difficulties in completing the problem. While the learning difficulty factor is caused by two factors that are internal and external factors. internal factors include: a) lack of interest in students, b) lack of motivation to learn, c) lack of confidence to ask. External factors, among others: a) The class atmosphere is not conducive, b) the influence of handphone in the student concentration, c) lack of parental assistance in supervision at home.